Berjalan Bersama dengan TERANG: Strategi Mentoring PPL untuk Membangun Kompetensi Mahasiswa PPG Menuju Guru Profesional - Dwi Hartini (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The TERANG approach (Tentukan tujuan/Determine goals, Eksplorasi kondisi/Explore conditions, Rancang pilihan/Design options, Ambil keputusan/Take action, Nilai dan refleksikan/Evaluate and reflect, Gerakkan perubahan/Mobilize change) represents an innovative best practice in mentoring pre-service peacher professional pducation (PPG Prajabatan) students, specifically aimed at strengthening their professional competence as future educators. This initiative was motivated by the finding that students often remain passive and struggle with data interpretation in statistics learning. The primary objective of this action research was to enhance the PPG students' reflective skills while simultaneously improving the quality of student learning through the application of project-based learning utilizing real-world data. This study employs a collaborative reflective action approach between the mentoring teacher and the PPG students, systematically executed through the six TERANG stages. The findings reveal that the initial stages, Determine Goals and Explore Conditions, were effective in cultivating the students' reflective awareness regarding the necessity of contextual and meaningful learning. The Design Options and Take Action stages successfully generated data literacy project designs which significantly increased student engagement, fostered critical thinking skills, and developed a sense of learning responsibility. The Evaluate and Reflect stage documented a 15% increase in students' data interpretation ability, coupled with markedly higher enthusiasm in group activities. Despite this progress, a weakness was identified in students' verbal communication skills, indicating a need for targeted improvement through data presentation and debate activities. The final stage, Mobilize Change, served as a critical moment for PPG students to execute a second improvement cycle by incorporating